Whole-body cooling of hyperthermic runners: comparison of two field therapies - Armstrong, L. E.; Crago, A. E.; Adams, R.; Roberts, W. O.; Maresh, C. M. (1996)
Severe exercise-induced hyperthermia requires rapid cooling. Of the many cooling modalities available, there is disagreement over which is the most effective. The purpose of this field study was to compare two cooling therapies for hyperthermic distance runners who had completed an 11.5-km summer foot race. Twenty-one distance runners (mean [+/- SE] initial rectal temperature 41.2 +/- 0.2 degrees C) were treated either by ice water immersion (1 to 3 degrees C, n = 14) or by air exposure while wrapped in wet towels (24.4 degrees C ambient, n = 7). Ice water immersion versus air exposure resulted in significantly different (P < .005) pretherapy to posttherapy changes in rectal temperature (-3.0 +/- 0.3 v -1.4 +/- 0.3 degrees C) and mean cooling rate (0.20 +/- 0.02 v 0.11 +/- 0.02 degrees C/min). Ice water immersion cooled approximately twice as fast as air exposure. These data refute the theory that ice water immersion is an inefficient cooling modality. Am J Emerg Med 1996 Jul;14(4):355-8